Molecular Docking Study of Nutmeg (Myristica Fragrans) Constituents as Anti-Skin Cancer Agents - Fitriani, Ika Nur; Ansory, Hery Muhamad (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2021)
Molecular docking analysis was carried out to understand better the interaction between DHODH and inhibitor from nutmeg in this series. The nutmeg constituent binding orientations in the active site of DHODH was seen in a molecular docking analysis and helped design a potentially new inhibitor. This work aimed to study the molecular docking of nutmeg constituents with the DHODH inhibitor using a computer-aided drug design. Molecular docking using AutoDock 4.2 was done to explore the models of binding complexes. The 3D structure was derived using Discovery Studio to investigate the essential chemical interaction of complex structures. Dihydroguaiaretic acid was the most potent ligand having a docking score of -9.3 kcal/mol. This value was better than the standard drug 5-FU. The dihydroguaiaretic acid structure interacted with Tyr365 and Thr63 through a hydrogen bond similar to the native ligand. These results suggest that nutmeg seed could serve as the lead compound for potent DHODH inhibitors against skin.